2020
DOI: 10.1002/ppul.24935
|View full text |Cite
|
Sign up to set email alerts
|

Nasal high‐frequency percussive ventilation vs nasal continuous positive airway pressure in newborn infants respiratory distress: A cross over clinical trial

Abstract: Objective To determine if nasal high‐frequency percussive ventilation (nHFPV) to manage neonatal respiratory distress decreases the regional cerebral oxygen saturation (rScO2) compared to nasal continous positive airway pressure (nCPAP). Study Design A prospective, randomized, monocentric, open‐label, noninferiority crossover trial. Newborns of gestational age (GA) ≥ 33 weeks exhibiting persistent respiratory distress after 10 minutes of life were treated with nHFPV and nCPAP, in succession and in random order… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Only small case series exist in neonates ventilated with HFPV ( Pfenninger and Gerber, 1987 ; Pfenninger and Minder, 1988 ; Paviotti et al, 2014 ), but have demonstrated improvements in oxygenation without increasing airway pressures ( Pfenninger and Gerber, 1987 ; Paviotti et al, 2014 ), and improved static compliance ( Pfenninger and Minder, 1988 ). Nasal high-frequency percussive ventilation has recently been popularized ( De La Roque et al, 2011 ; Moresco et al, 2020 ; Renesme et al, 2020 ) and compared with nasal continuous positive airway pressure, demonstrated non-inferiority ( Renesme et al, 2013 ), possible benefit, and that it is well-tolerated ( De La Roque et al, 2011 ). In a piglet model of meconium aspiration syndrome, HFPV and CV were associated with lower mean airway pressures and OI as compared with HFOV, but there was no apparent difference in histologic lung injury ( Renesme et al, 2013 ).…”
Section: Neonatal High-frequency Percussive Ventilationmentioning
confidence: 99%
“…Only small case series exist in neonates ventilated with HFPV ( Pfenninger and Gerber, 1987 ; Pfenninger and Minder, 1988 ; Paviotti et al, 2014 ), but have demonstrated improvements in oxygenation without increasing airway pressures ( Pfenninger and Gerber, 1987 ; Paviotti et al, 2014 ), and improved static compliance ( Pfenninger and Minder, 1988 ). Nasal high-frequency percussive ventilation has recently been popularized ( De La Roque et al, 2011 ; Moresco et al, 2020 ; Renesme et al, 2020 ) and compared with nasal continuous positive airway pressure, demonstrated non-inferiority ( Renesme et al, 2013 ), possible benefit, and that it is well-tolerated ( De La Roque et al, 2011 ). In a piglet model of meconium aspiration syndrome, HFPV and CV were associated with lower mean airway pressures and OI as compared with HFOV, but there was no apparent difference in histologic lung injury ( Renesme et al, 2013 ).…”
Section: Neonatal High-frequency Percussive Ventilationmentioning
confidence: 99%